The political pathology of health care policy in South Africa - Retha Gaigher (Acta Academica)
South Africa is currently dealing with the transformation of health care into an equitable, national health care system driven by a primary health care approach. This requires a complicated sec of administrative and, in particular political changes. The problem is exacerbated by the fact that several of the visible changes in health care hastily implemented to make good on election promises did not result from policies based on genuine community needs. This article argues that the main reason for the presence of chis health care pathology is that the government has tried to effect transformation by means of hastily constructed visible changes, despite the absence of the structures needed to drive and support these changes. It also attempts to explain why a sizeable sector of the population is unable to experience the transformation of health care as an improvement.